Dental Man Power and Its Current Trend - Kasthuripriya, K.; Shrienitha, D. N. (International Journal Of Drug Research And Dental Science, 2023)
India is the seventh largest country in the world with a population of 1.2 billion. Dental health care is not integrated with general health care in most of the public health care setups and it is not provided at the primary health care level; it is provided to some extent at the secondary level but mostly at the tertiary care centers. Dental diseases are a significant public health burden in India, with dental caries affecting 60-65% of the general population. The availability of skilled human resources is critical for efficient healthcare system. Currently, the dentist population ratio has significantly improved for the past five years. An organized national human resource planning system is required to ensure consistent manpower allocation and to provide policymakers with future directions.